2021
DOI: 10.1002/eqe.3478
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a new kind of double‐layer shaking table

Abstract: Existing large‐scale electrohydraulic shaking tables (EHSTs) have limited frequency bandwidth because of the capacity of electrohydraulic systems. Here we propose a double‐layer shaking table (DLST) which is capable of generating excitations over a wide band of frequencies. The lower table is a conventional EHST with a long‐stroke actuator which can generate low‐frequency excitations. The upper table is fixed atop the lower table, and equipped with a short‐stroke actuator which can generate high‐frequency exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The three variable controller mainly consists of three variable feedback and feedforward controllers. 36,39 The three variable feedback controller is to collect the displacement and acceleration feedback signals of the shaking table in realtime to synthesize the velocity signals and transmit the three-state feedback signals to the servo-hydraulic controller to calculate the next step driving command. The advantage of velocity and acceleration feedback is to improve the resonance frequency and damping ratio while keeping the stability of the system.…”
Section: Tvcm-vpf For Ststmentioning
confidence: 99%
“…The three variable controller mainly consists of three variable feedback and feedforward controllers. 36,39 The three variable feedback controller is to collect the displacement and acceleration feedback signals of the shaking table in realtime to synthesize the velocity signals and transmit the three-state feedback signals to the servo-hydraulic controller to calculate the next step driving command. The advantage of velocity and acceleration feedback is to improve the resonance frequency and damping ratio while keeping the stability of the system.…”
Section: Tvcm-vpf For Ststmentioning
confidence: 99%
“…Notably, RTHT can be conducted with servo-hydraulic actuators, 7 shaking tables, 8 or a combination of the two. 9 To conduct RTHT, three problems must be properly addressed: (1) the computation of the numerical substructures should be efficient and stable; (2) the loading of the experimental substructure should be accurate and have low latency; (3) the communication between the substructures should be synchronized and have a small time delay.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies play an important role in civil engineering research. Structural testing techniques fall into three main categories: quasi‐static tests, 1 shaking table tests, 2 and hybrid tests 3 . Quasi‐static testing mainly adopts the static cyclic test method, which can obtain the hysteretic properties of the structure and provide design guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Some typical structures usually not only have large weights but also have high base frequencies, such as dams (Shi et al, 2014), nuclear power plants (Chang et al, 2020), and masonry buildings (Foraboschi and Vanin, 2013). In addition, for complex structures such as large-span grid structures (Tian et al, 2017), the effects of high-order modes and low-order modes need to be considered at the same time, and the dynamic response of structures subjected to ground motions with different spectra need to be considered, which puts forward higher requirements for the frequency bandwidth of the excitation signal (Pan et al, 2021). Thus, there is an urgent demand for a large-scale seismic simulation shaking table that can reproduce target signals with a wide frequency range and large load capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the feasibility of the proposed frequency splitting schemes and OIC method was verified by a series of numeric simulations and experiments. Pan et al (2021) compared the effects of two signal-separation methods and found that the FFT-IFFT method was better. Then, the FFT-IFFT method was used to separate the control signal, and the three-variable control (TVC) algorithm with feedforward compensation was used to control the double-layer shaking table.…”
Section: Introductionmentioning
confidence: 99%